2023
DOI: 10.1007/s00520-023-07928-8
|View full text |Cite
|
Sign up to set email alerts
|

Living with metastatic breast cancer (LIMBER): experiences, quality of life, gaps in information, care and support of patients in the UK

Abstract: Purpose To determine the experiences, information, support needs and quality of life of women in the UK living with metastatic breast cancer (MBC) to provide content for educational materials. Methods An online survey, hosted for 3 months on a UK MBC charity website, comprised sections covering issues such as communication about MBC treatment and management, helpful and less helpful things that healthcare professionals, family and friends did or sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Post-RT, a feeling of abandonment due to the burden of ongoing SE further exacerbates this dissatisfaction [66] . Failure to address a patient's needs and consider their lifestyle contributes to a substandard QoL, lower than they had expected [37] .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Post-RT, a feeling of abandonment due to the burden of ongoing SE further exacerbates this dissatisfaction [66] . Failure to address a patient's needs and consider their lifestyle contributes to a substandard QoL, lower than they had expected [37] .…”
Section: Resultsmentioning
confidence: 98%
“…While several studies have reported that patients have a greater desire for information before commencing RT [11] , [33] , [37] , [39] , [72] , [73] , there may be merit to reinforcing information provisions at various stages to strengthen the patient's comprehension [43] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations